Anticancer function of microRNA‐30e is mediated by negative regulation of HELLPAR, a noncoding macroRNA, and genes involved in ubiquitination and cell cycle progression in prostate cancer. Issue 16 (14th June 2022) - Ganapathy, Kavya; Ngo, Christopher; Andl, Thomas; Coppola, Domenico; Park, Jong; Chakrabarti, Ratna
Abstract : Prostate cancer (PCa) progression relies on androgen receptor (AR) function, making AR a top candidate for PCa therapy. However, development of drug resistance is common, which eventually leads to development of castration‐resistant PCa. This warrants a better understanding of the pathophysiology of PCa that facilitates the aberrant activation of key signaling pathways including AR. MicroRNAs (miRNAs) function as regulators of cancer progression as they modulate various cellular processes. Here, we demonstrate a multidimensional function of miR‐30e through the regulation of genes involved in various signaling pathways. We noted loss of miR‐30e expression in prostate tumors, which, when restored, led to cell cycle arrest, induction of apoptosis, improved drug sensitivity of PCa cells and reduced tumor progression in xenograft models. We show that experimental upregulation of miR‐30e reduces expression of mRNAs including AR, FBXO45, SRSF7 and MYBL2 and a novel long noncoding RNA (lncRNA) HELLPAR, which are involved in cell cycle, apoptosis and ubiquitination, and the effects could be rescued by inhibition of miR‐30e expression. RNA immunoprecipitation analysis confirmed direct interactions between miR‐30e and its RNA targets. We noted a newly identified reciprocal relationship between miR‐30e and HELLPAR, as inhibition of HELLPAR improved stabilization of miR‐30e. Transcriptome profiling and quantitative real‐time PCR (qRT‐PCR) validation of miR‐30e‐expressing PCa cells showed differential expression of genes involved in cell cycle progression, apoptosis and ubiquitination, which supports our in vitro study. This study demonstrates an integrated function of miR‐30e on dysregulation of miRNA/lncRNA/mRNA axes that may have diagnostic and therapeutic significance in aggressive PCa. Abstract : This study describes a tumor suppressor role of microRNA miR‐30e in prostate cancer (PCa), mediated by modulation of AR signaling, cell cycle, apoptosis and ubiquitination pathways. This is achieved by regulating direct mRNA effectors (AR, FBXO45, SRSF7, and MYBL2), indirect mRNA effectors, and a novel long noncoding RNA (lncRNA) HELLPAR . The function of miR‐30e impacts PCa progression through a microRNA‐mRNA‐lncRNA regulatory network.